The influence of the end shape of the liquid jet on its impact onto a dry wall - A.A. Aganin; T.S. Guseva (Учёные записки Казанского университета: Серия Физико-математические науки)
The influence of the end shape of a jet normally impacting onto a rigid wall on the characteristics of a shock wave in liquid and the pressure pulses on a wall has been studied. The water jet is axisymmetric, its end is hemispheroidal, with semi-axes R and бR where R is the jet radius, б varies from 0 through 2. The jet speed is 250 m/s. The dynamics of the liquid in the jet and the surrounding gas is governed by the Euler equations in the density, velocity, and pressure. Their solution has been derived numerically by the CIP-CUP method on an adaptive Soroban-grid without explicit separation of the liquid-gas interface. It has been found that for б > 0.38 the jet action on the wall before the shock wave detachment is similar to that of a hemispherically-ended jet with a radius of R/б. Qualitative differences from the hemispherically-ended jet case after the shock wave detachment are caused by the jet end non-sphericity at a distance from the jet axis. For all the considered values of б, the mean level of the wall pressure remains close to that in the hemispherically-ended jet case (б = 1). With decreasing б, the characteristic size of the maximum pressure load area and the radius of its central part with the quasi-uniform load increase.